2018
DOI: 10.1101/488726
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resolving the insertion sites of polymorphic duplications reveals aHERC2haplotype under selection

Abstract: Polymorphic duplications in humans have been shown to contribute to phenotypic diversity. However, the evolutionary forces that maintain variable duplications across the human genome are largely unexplored. To understand the haplotypic architecture of the derived duplications, we developed a linkage-disequilibrium based method to detect insertion sites of polymorphic duplications not represented in reference genomes. This method also allows resolution of haplotypes harboring the duplications. Using this approa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…This result is consistent with that of a previous study that suggested that African populations retain more ancestral sequences, which can lead to the misinterpretation of the unbalanced SV loads between African and non-African populations [9]. Third, the variants exert putative functional effects by introducing structural changes to genes or by modifying regulatory elements [43,44].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is consistent with that of a previous study that suggested that African populations retain more ancestral sequences, which can lead to the misinterpretation of the unbalanced SV loads between African and non-African populations [9]. Third, the variants exert putative functional effects by introducing structural changes to genes or by modifying regulatory elements [43,44].…”
Section: Discussionsupporting
confidence: 91%
“…Compared to variants reported by the 1KGP, the ratio of GWASassociation of non-reference insertions was similar to SNPs, indels, and SVs, whereas it was not similar for duplications. The depletion of linkage between duplications and GWAS-associated SNPs is attributed to the gap between the duplicated sites and the genomic locations where the duplications are inserted [45], which indicates the importance of the detection of insertion sites in the functional analysis of SVs [43]. By adding the insertion variants into the current catalogue of SVs, we could enhance the potential for detection of novel phenotypic associations; additionally, certain variants were observed to perform putative regulatory functions by affecting the expression of the corresponding genes.…”
Section: Discussionmentioning
confidence: 99%
“…The size, modularity, and functional potential of SVs may offer a rich substrate for natural selection, as supported by several specific examples of adaptive insertions and deletions in diet and pigmentation-related genes (Hsieh et al, 2019;Kothapalli et al, 2016;Perry et al, 2007;Saitou and Gokcumen, 2019), as well as genome-wide evidence from primarily short-read data (Almarri et al, 2020;Sudmant et al, 2015).…”
Section: Introductionmentioning
confidence: 99%